Kamisama kiss. Vol. 19 - Suzuki, Julietta; Kimura, Tomo (Shojo beat manga., 2015)
The school trip to Okinawa is turning out to be the opposite of a good time for Nanami and her friends. A terrible storm has shut down the island, and it turns out the bad weather is being caused by an enraged mermaid who won't rest until her stolen robe of feathers is returned. Nanami tries to get the robe back from Kirihito, who takes it to help him rescue his body from the Land of the Dead, but ends up drained of her vital energy! Can her shinshi Tomoe and Mizuki put aside their differences long enough to save their kamisama, or is Okinawa doomed?!